2019
DOI: 10.3947/ic.2019.51.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Antimicrobial Susceptibility Trends inCitrobacterBacteremia: An 11-Year Single-Center Experience

Abstract: Background Recently, Citrobacter freundii bacteremia outbreak in a neonatal intensive care unit has attracted public attention in Korea. However, Citrobacter bacteremia is uncommon and usually occurs in patients with underlying diseases such as malignancy and hepatobiliary diseases. Increase in resistance and emerging of multidrug resistance among Citrobacter species have gradually been reported. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…It has been reported to cure C. freundii infections even when other drugs have failed [ 113 ]. Over 70% of Citrobacter isolates in a 11-year single center study were reported to be susceptible to cotrimoxazole [ 60 ]. Neomycin has also been reported to clear infections caused by C. freundii [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to cure C. freundii infections even when other drugs have failed [ 113 ]. Over 70% of Citrobacter isolates in a 11-year single center study were reported to be susceptible to cotrimoxazole [ 60 ]. Neomycin has also been reported to clear infections caused by C. freundii [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both A. hydrophila and C. freundii have been shown to be susceptible to neomycin and cotrimoxazole in the planktonic phase [ 60 , 61 , 62 , 63 , 64 ]. We have previously predicted using whole genome sequencing that A. hydrophila RIT668 contains resistance genes for six classes of antibiotics, while C. freundii RIT669 contains resistance genes for 19 classes of antibiotics [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic bacteria that share homology with SARS-CoV-2 are K. pneumoniae, K. grimontii, E. coli, S. Enteritidis, E. faecalis, S. aureus, C. freundii, C. difficile, C. haemolyticum and C. novyi. They can cause infections ranging from common to rare and previous research has demonstrated T cell involvement in combatting the infections (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). They also have the potential to respond via heterologous mechanisms to cross-reactive epitopes and some of these bacteria have been isolated from the lower airways of COVID-19 patients (Table S3).…”
Section: Sars-cov-2 Protein Homology With Pathogenic Bacteriamentioning
confidence: 99%
“…The outcome variable was defined as mortality, which included mortality in the ED, hospital mortality after admission. Discharge with almost no chance of recovery and the expectation of death in the short term were also regarded as mortality [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%